2011
DOI: 10.1108/17554211111142194
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of “green” procurement

Abstract: PurposeThe purpose of this paper is to help readers understand the nature of the food supply chain and the way that environmental “costs” are accumulated along its length, with a view to developing more sustainable supply chains from political, social, economic technological and environmental perspectives.Design/methodology/approachIn order to do this, the authors have examined elements of the supply chain starting off by looking at consumer expectations and moving on to the environmental impact of different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Rad et al (2013) found that the outsourcing decisions of companies have significantly reduced carbon emissions. Beer and Lemmer (2011), Tidy et al (2016) and Cerutti et al (2016) analyzed carbon emission issue in food procurement. Hsu, Kuo, Shyu and Chen (2014) considered energy efficiency of products, eco-labeling, carbon accounting, energy reduction strategy, carbon governance and transport efficiency as criteria for selecting suppliers for the hotel industry.…”
Section: Classification By Contextmentioning
confidence: 99%
“…Rad et al (2013) found that the outsourcing decisions of companies have significantly reduced carbon emissions. Beer and Lemmer (2011), Tidy et al (2016) and Cerutti et al (2016) analyzed carbon emission issue in food procurement. Hsu, Kuo, Shyu and Chen (2014) considered energy efficiency of products, eco-labeling, carbon accounting, energy reduction strategy, carbon governance and transport efficiency as criteria for selecting suppliers for the hotel industry.…”
Section: Classification By Contextmentioning
confidence: 99%
“…, 2014). Food types can affect the natural environment, due to the food production systems, transport distances from producers and consumers, waste management, and workers' conditions in the sectors involved (Beer and Lemmer, 2011). The situation is even more complicated in the agri-fresh food sector due to the perishability of products and the short shelf-life (Siddh et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2018). Finally, many firms in the FSC are small or medium-sized enterprises (SMEs) (Beer and Lemmer, 2011; Ghadge et al. , 2017) that may find it difficult to address sustainability challenges and implement practices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations